Inclusion Extended: Educators With Disabilities - Clayton E. Keller; Barbara L. Brock (Educational Considerations, 2007)
Although historically the focus of disability-related research in education has centered on special education and the inclusion of students with disabilities, schools also employ teachers, administrators, and other educational personnel who have disabilities. How these educators fare in the workplace is of growing concern. If inclusion of students with disabilities in classrooms is a desirable goal, should not the idea be extended to adults with disabilities? Our response to this question is a resounding “Yes!” [Introduction to the special issue.]
Keywords: Educators; disabilities; resources; inclusion; accommodations